Prospects of Protected Vegetable Cultivation Technologies in Punjab - Kaur, Kamalpreet; Kaur , Prabhjot; Dhaliwal, Ravinder Kaur; Singh, Kulbir (Indian Journal of Extension Education, 2018)
A survey was undertaken to study the prospects of protected vegetable cultivation technologies in Punjab covering six  districts viz. Amritsar, Gurdaspur, Sangrur, Moga, Jalandhar and Kapurthala. From these districts a total of 150  respondents were selected for the purpose of study by probability proportion of protected vegetable cultivation growers in  the selected districts. Data were collected by personal interview method. The prospects and satisfaction of the protected  vegetable growers were studied. Questions were asked from the farmers regarding the prospects of protected vegetable  cultivation. The results reveal that protected cultivation of vegetable gained importance since 2009 in Punjab because  majority of respondents adopt this technique during 2009-2013. The data further showed that 34.48 per cent of  respondents were willing to increase the area under protected vegetable cultivation due to profitable enterprise. While  maximum number of respondents (45.98%) wanted to keep the area constant under protected vegetable cultivation  technologies due to non availability of land to increase the area and unable to handle protected structures on more area.  Majority of respondents preferred poly house followed by net house for cultivation of vegetables and maximum number  of respondents were satisfied from this technology. It may be concluded that it is a profitable enterprise for farmers due to  off season production and high yield so maximum number of respondents were willing to keep the area constant or  increase the area under protected structures for vegetable cultivation.
Keywords: Prospects; protected cultivation; profitable; satisfaction